Implementasi Sistem IoT Monitoring Kualitas Udara Dalam Kelas Untuk Kenyamanan Pengguna Ruangan - Kelvyn Rosan; Fachrid Wadly; Muhammad Amin (CV. Hawari, 2025)
This study aims to design and buiId an Internet of Things (IoT)based air quality monitoring system that can be applied in classrooms to support the comfort and health of room users. This system integrates the NodeMCU ESP8266 microcontroIIer with a DHT11 temperature and humidity sensor, and an MQ-135 air quality sensor. The environmental data obtained is displayed in real-time via the Blynk application and an OLED LCD screen, making it easy to monitor without having to be on site. The design process was carried out using the Research and Development (R&D) method approach, which includes the stages of identifying needs, designing, implementing, and testing the system in the fieId. The test results show that the system is able to provide accurate and stable data with temperature and humidity measurement deviations that are still within tolerance limits. This system is expected to be a simple but effective solution to maintain classroom air circulation, while increasing awareness of the importance of air quaIity in educational environments.